Iris pseudomeda (Iridaceae), a new species of Iris section Oncocyclus from Iran - Salimbahrami, Mona; Saeidi, Hojjatollah; Bagheri, Ali (Phytotaxa, 2021)
Iris pseudomeda is described and illustrated as a new species of Iris section Oncocyclus from Kurdistan province in northwestern Iran. It occurs among subalpine flora of Zagros mountain range, on stony calcareous hillsides and the brink of grassland fields. A complete morphological description, conservation status, botanical illustrations, notes on habitat and distribution range are presented for the new species. Furthermore, taxonomic relationships of I. pseudomeda with other members of this rhizomatous bearded section, particularly I. meda, are also discussed.